1998
DOI: 10.1097/00005053-199802000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in Substance Abusers: Relation to Substance Use

Abstract: Previous studies have documented high but variable rates of DSM personality disorders (axis II) in clinical samples of substance abusers. Distinguishing between personality disorder symptoms that are independent versus substance-related (SR) is a particular challenge for diagnosing comorbid axis II disorders in substance abusers. DSM-IV guidelines currently recommend excluding axis II symptoms that are accounted for by an axis I disorder, including a substance use disorder. In this study, axis II diagnoses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
1
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(87 citation statements)
references
References 25 publications
2
78
1
6
Order By: Relevance
“…The body of research on substance abuse/dependence and personality disorders underscores the associations among these disorders. Multiple studies have identified high rates of comorbidity between Cluster B and substance use disorder diagnoses in treatment and community samples (Casillas & Clark, 2002;Taylor, 2005), even when substance abuserelated personality disorder criteria are removed (Rounsaville et al, 1998). In examining the longitudinal development of PGD, Slutske and colleagues (2005) found that "the personality profile associated with problem gambling was strikingly similar to the profiles associated with alcohol, cannabis, and nicotine dependence".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body of research on substance abuse/dependence and personality disorders underscores the associations among these disorders. Multiple studies have identified high rates of comorbidity between Cluster B and substance use disorder diagnoses in treatment and community samples (Casillas & Clark, 2002;Taylor, 2005), even when substance abuserelated personality disorder criteria are removed (Rounsaville et al, 1998). In examining the longitudinal development of PGD, Slutske and colleagues (2005) found that "the personality profile associated with problem gambling was strikingly similar to the profiles associated with alcohol, cannabis, and nicotine dependence".…”
Section: Discussionmentioning
confidence: 99%
“…Axis II disorders also display high levels of comorbidity with each other . Furthermore, theorists have identified a lack of diagnostic and conceptual clarity between substance abuse/dependence, PGD, and personality disorders (Blaszczynski et al, 1989;Rounsaville et al, 1998). These relationships complicate analysis of associations among these conditions.…”
Section: Pathological Gambling and Personality Disordersmentioning
confidence: 99%
“…17 BPD is perhaps the most common Axis II disorder in women with SUD, with prevalence ranging from 10% to 65%. [17][18][19][20] In the largest and most stringent study on the comorbidity of BPD in psychiatric patients to date, 59% of women with BPD had at least one lifetime SUD, including alcohol abuse or dependence, and 41% had at least one lifetime diagnosis of drug abuse or dependence. 21 In addition, BPD appears to be associated with new onsets of SUD, even in BPD patients who are in stable remission.…”
mentioning
confidence: 99%
“…24 Abuso de uma ou mais substâncias foram relatados por 76% de pacientes com transtorno da personalidade borderline (TPB) e por 95% dos pacientes com transtorno da personalidade anti-social (TPAS), em adultos jovens internados em um serviço psiquiátrico de hospital geral.…”
unclassified